An Analysis of Factors Affecting the Decision to Study in Luang Prabang Teacher Training College - xaiyalath, deuan-lin; SALITXAY, Timnoy; SOULIYA, Toulakone (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
This research aims to analyze the factors affecting students' decision-making regarding further education at Luang Prabang Teacher Training College. The sample consisted of 290 students. Data were collected using a 5-point Likert scale questionnaire and analyzed using descriptive statistics, including Mean and Standard Deviation. Inferential statistics, specifically Multiple Regression Analysis, were employed to test the hypotheses. The research findings revealed that the seven independent factors collectively predicted students' decision to pursue education at Luang Prabang Teacher Training College with statistical significance at the 0.05 level (R = 0.694). These factors together explained 48.10% of the variance in students' decision-making (R2= 0.481). When considering individual factors, two variables significantly influenced the decision at the 0.01 level: Personal Reasons (X1) and Future Opportunities (X7), which demonstrated the highest predictive power. Hypothesis testing confirmed that both factors have a significant positive impact on decision-making. Conversely, Institutional Environment/Quality (X2), Financial Factors (X3), Curriculum (X4), Family Factors (X5) and Social Factors (X6) did not significantly affect the decision-making process at the 0.01 level.